EFEK PENGGUNAAN TEPUNG DAUN MENGKUDU (Morinda citrifolia) DALAM RANSUM DENGAN LEVEL BERBEDA TERHADAP PERFORMANCE DAN IOFC TERNAK BABI - N. S., DALLE; TUKAN, H. D.; NUGRAHA, E. Y.; NDAU, W. A. (Majalah Ilmiah Peternakan, 2024)
This research aimed to evaluating effect of including noni leaves meal into basal diet on diet intake, weight gain, diet conversion and income overfeed cost (IOFC) in Landrace crossbred pig. There were 12 Landrace crossbred pigs 1-2 months old with 10.50-21.50kg (average 16.70kg) and coefficient of variation 18.76%. This research lasts for 8 weeks consisting of 2 weeks of adjustment and 6 weeks of data collection. The method used in this study is a direct experimental method using randomized block design which consists of 4 treatments and 3 replications so the num- ber of samples taken is 12 samples. The treatment diets offered were: R0: 100% basal diet without noni leaves meal; R1: 98% basal diet + 2% noni leaves meal; R2: 96% basal diet + 4% noni leaves meal; and R3: 94% basal diet + 6% noni leaves meal. Variable evaluated were diet intake, weight gain, diet conversion and IOFC. Statistical analyisis found used Microsoft excel that including noni leaves meal is not significant (P>0.05) in research variable. The conclusion is that including 2, 4, 6% noni leaves into basal diet giving relative the same influence both diet intake, weight gain, diet conversion and IOFC in Landrace crossbred pigs.